Neurodevelopmental outcome of low-risk moderate to late preterm infants at 18 months - Ryan, Mary Anne; Murray, Deirdre M.; Dempsey, Eugene M.; Mathieson, Sean R.; Livingstone, Vicki; Boylan, Geraldine B. (Frontiers in Pediatrics, 2023)
Of the 15 million preterm births that occur worldwide each year, approximately 80% occur between 32 and 36+6 weeks gestational age (GA) and these infants are defined as moderate to late preterm (MLP) infants. This percentage substantiates a need for a better understanding of the neurodevelopmental outcome of this group. To describe neurodevelopmental outcomes at 18 months in a cohort of healthy low-risk MLP infants admitted to the neonatal unit at birth and to compare the neurodevelopmental outcome to that of a healthy term-born infant group. This single-centre observational study compared the neurodevelopmental outcome of healthy MLP infants to a group of healthy term control (TC) infants recruited during the same period using the Griffith's III assessment at 18 months. Seventy-five MLP infants and 92 TC infants were included. MLP infants scored significantly lower in the subscales: Eye/Hand co-ordination (C), Personal/Social and Emotional Development (D), Gross Motor Development (E) and General Developmental Quotient (GD) (p<0.001 for each) and Foundations of learning (A), (p=0.004), in comparison to the TC infant group with Cohen's d effect sizes ranging from 0.460 to 0.665. There was no statistically significant difference in mean scores achieved in subscale B -language and communication between groups (p=0.107).MLP infants are at risk of suboptimal neurodevelopmental outcomes. Greater surveillance of the neurodevelopmental trajectory of this group of at-risk preterm infants is required.